Autophagy in ethanol-exposed liver disease. (September 2015) - Wang, Li-Ren; Zhu, Gui-Qi; Shi, Ke-Qing; Braddock, Martin; Zheng, Ming-Hua
Abstract : Ethanol metabolism in hepatocytes causes the generation of reactive oxygen species, endoplasmic reticulum stress and alterations in mitochondrial energy and REDOX metabolism. In ethanol-exposed liver disease, autophagy not only acts as a cleanser to remove damaged organelles and cytosolic components, but also selectively clears specific targets such as lipid droplets and damaged mitochondria. Moreover, ethanol appears to play a role in protecting hepatocytes from apoptosis at certain concentrations. This article describes the evidence, function and potential mechanism of autophagy in ethanol-exposed liver disease and the controversy surrounding the effects of ethanol on autophagy.